The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.12688/f1000research.5927.1
|View full text |Cite
|
Sign up to set email alerts
|

Student perception about working in rural United States/Canada after graduation: a study in an offshore Caribbean medical school

Abstract: Introduction: Rural residents of the United States (US) and Canada face problems in accessing healthcare. International medical graduates (IMGs) play an important role in delivering rural healthcare. IMGs from Caribbean medical schools have the highest proportion of physicians in primary care.  Xavier University School of Medicines admits students from the US, Canada and other countries to the undergraduate medical (MD) course and also offers a premedical program. The present study was conducted to obtain stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The earlier few studies have either considered a limited spectrum of items in the questionnaire or were conducted in developed nations. [ 4 , 12 , 16 , 17 , 35 , 36 ] After rigorous literature review and expert Delphi consultations, a questionnaire consisting of 33 items was developed which was named the MSDRI questionnaire. Interestingly, our analyses highlight 5 factors/subscales for the items listed in the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier few studies have either considered a limited spectrum of items in the questionnaire or were conducted in developed nations. [ 4 , 12 , 16 , 17 , 35 , 36 ] After rigorous literature review and expert Delphi consultations, a questionnaire consisting of 33 items was developed which was named the MSDRI questionnaire. Interestingly, our analyses highlight 5 factors/subscales for the items listed in the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Research activities at training institutions was intuitively and personally understood as a signal of educational quality, while the absence of research stood out as a concern. The absence of research programs at Caribbean offshore medical schools has been problematized elsewhere in the literature, 4 , 9 , 18 and thus participants are not alone in this concern. Some participants indicated that the lack of research engagement at offshore institutions is preventing those in the international medical education community from gaining familiarity with the quality and nature of training they offer through opportunities for research collaboration.…”
Section: Discussionmentioning
confidence: 99%
“… 3 - 7 Furthermore, undergraduate clinical training often takes place in the US due to limited capacity in the Caribbean. 7 - 9 The offshore medical school industry has grown substantially in recent decades; for example, 20 new offshore medical schools have opened since 2007, representing 36 percent of medical schools currently operating in the Caribbean. 2 In turn, this industry is quickly transforming the landscape of global medical education.…”
Section: Introductionmentioning
confidence: 99%
“…poor living conditions (Saini et al, 2012 (Pati et al, 2015) were listed by many authors. The shortage of basic amenities like electricity, water and telecommunication facilities(P Ravi Shankar et al, 2015) were indicated for frustration. Financial incentives, political interference, lack of drug supplies and poor accommodation facilities (Goel et al, 2019) (Goel, Angeli, Singla, & Ruwaard, 2018), Poor standard of living (Saini et al, 2012), rural areas are difficult place to work (Aydin et al, 2015)poorly functioning health facilities (Arscott-Mills et al, 2016), A lack of social amenities, financial and material resources; (Anthony Amalba et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…(Jain et al, 2016) were demonstrated in major works. The problem of schools for the education of children(P Ravi Shankar et al, 2015), lack of education opportunities for children (Jain et al, 2016) were mainly reasoned for non-acceptance of rural practice in future (Han & Humphreys, 2005). Lesser research opportunities (Goel et al, 2019) lack of learning opportunities (Arscott-Mills et al, 2016) difficult to gain experience (Tolhurst et al, 2008)in clinical practice is perceived as hindrances for their advancements.…”
Section: Methodsmentioning
confidence: 99%